THE MARKET OF ORGANIC FOOD PRODUCTION IN REPUBLIC OF MOLDOVA - Pavel MOVILEANU; Veronica MOVILEANU; Svetlana SASU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2013)
In this article the authors will analyze the development of Moldavian organic agriculture in European agriculture field. Organic farming is an agricultural system designed to provide consumers with fresh, tasty and authentic food, at the same time respecting the natural life cycle of the systems. Moldavian population needs organic production for its health and welfare. The authors consider the organic farming as a solution that is able to prevent a future food crisis, as world’s population is increasingly facing an acute shortage of food. Based on the literature in the field the authors describe the extension of certified organic areas in the period of 2003-2011, that had increased by 270 times from 80 ha to 22 102 ha. Moldavian local market of selling the organic products is almost non-existent because of the small farming practice in the country. The conclusion is that the premises for the development of national organic sector should be connected, exclusively to export markets at least for medium term. These are mature and can "digest" the local organic products, offering fair prices to local producers.